Configuration of Zeros of Isochronous Vector Fields of Degree 5 - Julio Cesar Avila; Montserrat Corbera; Martín Eduardo Frías–Armenta (Complexity)
In this paper, we give the algebraic conditions that a configuration of 5 points in the plane must satisfy in order to be the configuration of zeros of a polynomial isochronous vector field. We use the obtained results to analyze configurations having some of its zeros satisfying some particular geometric conditions.